A Case Study of Parental Involvement in Fostering Their Child’s English-Speaking Skills - Wulandari, Bunga Ayu; Heryanti, Reny; Usman, Rizki Dwiki Reza; Ridha, Ahmad; Fortunasari, Fortunasari (Universitas Jambi, Indonesia, 2022)
This research investigates how parents support their children's English language development. Interviews with the parents of a nine-year-old Indonesian girl named Acha (pseudonym) were conducted to learn more about how they perceived their involvement in their daughter's development of English-speaking abilities. When the research was conducted, Acha was a third grader at an elementary school with 364 subscribers on her YouTube channel. Her competence in speaking English is exhibited in her YouTube videos. This research indicates that Acha’s English language acquisition process has involved her parents’ interventions directly and indirectly. This research reveals several helpful practices performed by Acha's parents, including early exposure to simple vocabulary, a positive home literacy environment (HLE) situation, encouragement of Acha to use English, and facilitation of Acha's access to English-language YouTube content. According to the results of this research, Acha's parents' practices are mediated by their educational experiences, socioeconomic status, and digital literacy skills. This research demonstrates the beneficial effects of parental participation on children's language development.